Síntese diastereosseletivas e atividades antinociceptivas de novos derivados tetraidropirânicos substituídos - Capim, Saulo Luis (2013)
This work is described the synthesis of ten new tetrahydropyran derivatives (compounds 42-51) designed from (±)-Naproxen structure utilizing the Prins reaction of cyclization as the key step to building shaped diastereoselective 2,4- cis and 2,4,6-cis rings tetrahydropyran, with overall yields between 62 - 65%. These new tetrahydropyran derivatives were in vivo bioevaluated on antinociceptive effect in the acetic acid-induced abdominal writhing test, the tail flick test, the rota-rod performance and open field tests, and all these new compounds showed greater antinociceptive activity compared to compound (±)- 1a, highlighting high activity tetraidropirânico derivative (±)-49, which showed 87.5% of inhibition, whereas compound (±)-1a gave only 14% inhibition in in the acetic acid-induced abdominal writhing test. Moreover, the (tail-flick test) indicated compounds (±)-46 and (±)-49 as the most actives, and all compounds showed antinociceptive activity (except compound (±) -51) without harming the motor impairment and without showing toxicity in mice. In continuation to this work, there was the synthesis of new hybrid molecules based on the structure of six non-steroidal anti-inflammatory drugs with a portion tetrahydropyran using molecular hybridization strategy. These new hybrid tetrahydropyran (74 - 79) were obtained in yields between (70 - 93%). Preliminary studies antinociceptive effect in the acetic acid-induced abdominal writhing test in the compounds (74 - 79) showed that all tetrahydropyran derivatives were more efficacious (lower ED50) and their precursors drugs and no sign of intoxication were observed in the animals.